ANALISIS PENGARUH INFLASI, NILAI TUKAR RUPIAH, DAN BI RATE TERHADAP NILAI AKTIVA BERSIH REKSADANA SYARIAH DI INDONESIA (PERIODE 2015-2019) - Namira Azalia; Raden Bambang Budhijana (Journal of Accounting, Management and Islamic Economics, 2023)
This research examined the analysis of the effect of the Inflation, Rupiah Exchange Rate and BI Rate on the Net Asset Value (NAV) of Islamic Mutual Fund. Data used in this research is annualy, data start from 2015 until 2019. Sampling method used in this research is purposive sampling. This research used quantitative approach method and the analysis techniques used is multiple linear regression that using Eviews Version 10. Based on the result of this research showed that Inflation, Rupiah Exchange Rate and BI Rate stimultaneously has significant effect to Net Asset Value (NAV) of Sharia Mutual Balanced Fund. The results also show that inflation has a significant negative effect on the NAV of Islamic mutual funds. The Rupiah Exhange Rate (Exchange Rate) has a significant negative effect on the NAV of Islamic mutual funds and Bank Indonesia (BI) Rate significant positive effect of the NAV of Islamic mutual funds.